The Detection of Encoding Gene of Toxic Shock Syndrome Toxin-1 S. aureus Isolate from the Milk of Cows and Goats by Polymerase Chain Reaction - Rony M Kunda; A.E.T.H. Wahyuni; Rini Widayanti (Jurnal Sain Veteriner, 2013)
Abstract Staphylococcus aureus is the main bacterium found in cow's and goat's milk. The bacteria can produce toxin called toxic shock syndrome toxin-1 (TSST-1) that can infect humans and animals causing several serious diseases. The objective of this study was to detect the existence of encoding gene of TSST-1 S. aureus isolate from cow's and goat's milk. The research is initiated by re-identification stage of S. aureus conventionally continued by identification based on the molecular method of polymerase chain reaction (PCR). A number of 10 S. aureus isolates from cow's and goat's milk cultured in aerobics continued by Gram stain, catalase, coagulase, MSA, VJA and VP tests. The identification of S. aureus based on the molecular approach conducted by 16S rRNA gene amplification continued with amplification of TSST-1 encoding gene as the target gene. The PCR product of TSST-1 encoding gene then sequenced to ensure whether the DNA fragment amplified is the TSST-1 encoding gene or not. The result of the research indicates that re-identification of S. aureus conventionally generating positive reaction of S. aureus species. Molecular identification of 16S rRNA gene amplification gives a good result by producing DNA fragment of 745 bp size and meets the target gene. The detection result of encoding gene TSST-1 gives negative result marked by DNA fragment which the size does not match the target gene. The allignment result of sequence isolate SA.1 indicates that the sequence is not tst gene but the gene which coded glutamate sinthetase belongs to S. aureus, whereas sequence of isolate KI.8 is 50S rRNA gene belongs toS. saprophyticus.